Interaction of designed cationic antimicrobial peptides with the outer membrane of gram-negative bacteria - Shelley He; Charles M. Deber (Scientific Reports, 2024)
Abstract The outer membrane (OM) is a hallmark feature of gram-negative bacteria that provides the species with heightened resistance against antibiotic threats while cationic antimicrobial peptides (CAPs) are natural antibiotics broadly recognized for their ability to disrupt bacterial membranes. It has been well-established that lipopolysaccharides present on the OM are among major targets of CAP activity against gram-negative species. Here we investigate how the relative distribution of charged residues along the primary peptide sequence, in conjunction with its overall hydrophobicity, affects such peptide-OM interactions in the natural CAP Ponericin W1. Using a designed peptide library derived from Ponericin W1, we determined that the consecutive placement of Lys residues at the peptide N- or C-terminus (ex. “PonN”: KKKKKKWLGSALIGALLPSVVGLFQ) enhances peptide binding affinity to OM lipopolysaccharides compared to constructs where Lys residues are interspersed throughout the primary sequence (ex. “PonAmp”: WLKKALKIGAKLLPSVVKLFKGSGQ). Antimicrobial activity against multidrug resistant strains of Pseudomonas aeruginosa was similarly found to be highest among Lys-clustered sequences. Our findings suggest that while native Ponericin W1 exerts its initial activity at the OM, Lys-clustering may be a promising means to enhance potency towards this interface, thereby augmenting peptide entry and activity at the IM, with apparent advantage against multidrug-resistant species.